An interesting variation in the fifth lumbar vertebra - Chorn, David J.; Rule, Lucy-May (Polskie Towarzystwo Antropologiczne, 1994)
Variations in the lumbosacral region of the vertebral column are frequent and well documented [Hibbs, Swift 1929; Horwttz, Smith 1940; Nathan, Arensburgh 1972]. Ten percent of patients presenting with symptoms of low back-pain are found to have some segmental anomaly of the lumbosacral spine [McCulloch, Waddell 1980]. In the present report, an interesting variation of the fifth lumbar, vertebra (L5) is described and appraised with respect to its embryology and its possible functional significance.